Implementasi Rekomendasi Financial Action Task Force (FATF) Dalam Sektor Notaris ditinjau Dari UUJN: (Studi di MPD Deli Serdang) - Ibnu Syuaif Rangkuti (CV Rewang Rencang, 2025)
Notary as a member of the Financial Action Task Force (FATF) to eradicate money laundering. At the level of the Notary Regional Supervisory Council which has the authority and obligation to carry out guidance and supervision of Notaries in the Region (Regency/City Level). In the research location at MPD Deli Serdang. This research method is a type of empirical juridical research. The results of the research and discussion are that the main basis that supports the involvement of a notary is as a Gatekeeper through the Implementation of Beneficial Owner Recognition. Implementation of these recommendations in Serdang delis faces obstacles, such as Capacity and Knowledge Constraints: Not all notaries fully understand FATF regulations or have adequate training regarding the obligation to report suspicious transactions.